Applications of submerged and staged membrane systems for pollutant removal from effluents and mechanism studies – a review. (August 2022) - Sivaprakash, Baskaran; Rajamohan, Natarajan; Reshmi, Angelin; Annadurai, Abitha; Varjani, Sunita
Abstract: Membrane based filtration is one of the promising technologies for rehabilitation of wastewater streams for reuse and recycle. Many advancements have emerged with the use of novel materials and innovative integrated technologies. The present investigation focuses on the treatment methods based on submerged and stages systems of membranes for water purification. Ceramic, polymeric and mixed matrix type of membranes fabricated for specific type of effluents, their modification methods for accelerating the rejection efficiency, permeability, durability, stability and antifouling properties are detailed in this review. Graphene oxide is the most considered membrane material for adsorption purposes as it exhibits larger surface area, abundant functional groups contain oxygen and has good supply of ligands which is responsible in metal adsorption as it enhances electrostatic interaction by bonding metal ions with graphene oxide nanosheets. Energy derivation in terms of biogas production was also reported in some integrated methods. In many cases, embedded nanomaterial matrices yielded maximum efficiencies in both the submerged and staged operations. However, submerged type of membranes are reported more than the staged type due to simpler configuration with relatively lesser equipment, operational and maintenance issues. In treatment of a low strength wastewater, aluminum oxide based membrane in fluidized bed assembly was reported to yield promising results with reduced power requirement. Graphical abstract: Image 1 Highlights: Comprehensive review on novel membrane system application for removal of pollutants is presented. Applications of submerged and staged membrane systems for wastewater treatment are discussed. Removal performance using embedded nano materials is explained. Bottlenecks and future perspectives on membrane research are presented.